TINJAUAN HUKUM ISLAM TERHADAP PENUKARAN UANG BARU MENJELANG HARI RAYA IDUL FITRI - Bariroh, Muflihatul (IAIN Tulungagung, 2016)
In Islam, money is not regarded as a commodity that can be traded as in the conventional economic system. Its utilization is limited as a medium of exchange and a measure of value. If a money in the same kind will be exchanged, the payment must be balanced and cash. The violation of these regulations resultsin the âfadlâ usury (Riba Fadl). This research was conducted on the basis of a fatwa Indonesian Ulema Council (MUI) Jombang East Java, which establishes the prohibition of new money exchange transactions before Idul Fitri for the indication of usury. While on the other hand, the practice is more wide spread and becomes a part of the wheels of the economy of Islamic society every Idul Fitri. The results of research show that consideration of Islamic law should be able to participate in shaping the public life and has the sensitivity to goodness (sense of maslahah). The author concludes that the practice of a new money exchange is allowed. As to the difference of exchanged money does not include the fadl usury, but it becomes wages (ujroh) which must be received by the provider of service as an income when waiting to exchange money in the bank.Keywords: Money, Usuary, Wages, Maslahah